Relação entre o fluxo luminoso interceptado em diferentes épocas no índice de área foliar de diferentes forrageiras - Montes Nogueira Borges, Bernardo Melo [UNESP]; da Silva Junior, Laurencio Caetano; Lucas, Fabio Teixeira [UNESP]; da Silva, Wilson Jesus (Universidade Estadual de Londrina (UEL), 2011)
The objective was to evaluate the leaf area index of six different grasses. The experiment was installed at the Instituto Federal de Tecnologia e Educacao of Uberaba, using a randomized block design with split plots in time. The plots were sown: Brachiaria decumbens cv. Basilisk, Brachiaria brizantha cv. Marandu, Panicum maximum cv. Mombasa, Panicum maximum cv. Tanzania, Brachiaria brizantha cv. Xaraes, Cynodon dactylon hb. Tifton and the plots, ten seasons of evaluation in 10 x 6 factorial arrangement with four replications. Rates of leaf area of each forage at different times of year were evaluated. Compared to other forage species, Panicum maximum had a higher leaf area index when subjected to periodic fertilization and irrigation. Only in the late fall Brachiaria Xaraes IAF had increased, but did not differ significantly from the others.
Relationship between luminous flux intercepted at different times in leaf area index of different forages
Keywords: Leaf area; times; grass